Pengaruh Akuntabilitas, Transparansi dan Partisipasi Masyarakat Terhadap Efektifitas Pengelolaan Dana Desa - Gema Syahriady; Marzuki Marzuki; Isthafan Najmi; Agusmadi Agusmadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
management of village funds in the village requires proper accountability, transparency and community participation. This study aims to examine the effect of accountability, transparency and community participation on the effectiveness of managing village funds. This research belongs to the category of quantitative research, the type of research used is associative. The population in this study were all heads of families in the village of Lambheu totaling 2079 families. While the research sample is100 people. The result shows that there are simultaneous influences of accountability, transparency and community participation on the effectiveness of managing village funds (Case Study of Gampong Lambheu, Darul Imarah District, Aceh Besar District). fcount value of 53.392 with a significant value of 0.001. The probability value (0.001) is less than 0.05. Partial testing also has an effect where tcount X1 > ttable (2.787> 1.986), tcount X2 > ttable (3.444> 1.986), and tcount X3 > ttable (3.099> 1.986). Meanwhile, the moderation test is known to strengthen the influence of the independent variables on the dependent variable. The R-square coefficient is 0.625, meaning 62.5%, the proportion of changes in village fund management can be explained by changes in the variables of accountability, transparency and community participation. From this study it can be seen that there is a simultaneous and partial influence.